2019
DOI: 10.1038/s41598-019-41629-9
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell TNFR1 signaling dependent liver injury and inflammation upon BCG infection

Abstract: TNF plays a critical role in mononuclear cell recruitment during acute Bacillus Calmette-Guérin (BCG) infection leading to an effective immune response with granuloma formation, but may also cause tissue injury mediated by TNFR1 or TNFR2. Here we investigated the role of myeloid and T cell specific TNFR1 and R2 expression, and show that absence of TNFR1 in myeloid cells attenuated liver granuloma formation and liver injury in response to acute BCG infection, while TNFR2 expressed in myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
(56 reference statements)
1
20
0
Order By: Relevance
“…Here, we demonstrated that a small fraction of circulating monocytes from a healthy donor is typically differentiated into CD3 + MDM, and this cell subpopulation can be divided into TCRαβ + and TCRαβ − phenotypes, both subpopulations has been recently reported in mice and they are negative to CD2 (12). In this regard, we found both proteins and mRNA transcripts for TCR chains in each MDM subpopulation, suggesting that MDM have the ability to express TCR on macrophages under an appropriate stimulus.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Here, we demonstrated that a small fraction of circulating monocytes from a healthy donor is typically differentiated into CD3 + MDM, and this cell subpopulation can be divided into TCRαβ + and TCRαβ − phenotypes, both subpopulations has been recently reported in mice and they are negative to CD2 (12). In this regard, we found both proteins and mRNA transcripts for TCR chains in each MDM subpopulation, suggesting that MDM have the ability to express TCR on macrophages under an appropriate stimulus.…”
Section: Discussionmentioning
confidence: 70%
“…Previously, our group and other have reported that TNF is required to generate TCRαβ + macrophages after in vitro BCG infection, and apparently TNFR1 expression is necessary to maintain the presence of CD3 + myeloid cell (11, 12). Additionally, our data have shown that CD3 + TCRαβ + MDM expressed tmTNF (Figure 3D).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations